Digital reading: evolution or revolution - Alonso-Arévalo, Julio; Cordón, José-Antonio (Anuario ThinkEPI, 2012)
Book digitization is having a significant impact at all economic, business and legal levels. Concepts that had prevailed since the advent of the printing press more than 500 years ago have to be changed. With self-publishing, authors do not need publishers, and some indie (independent) are getting an enthusiastic public reception, selling hundreds of thousands of copies. For their part, publishers, who traditionally had been confined to one language and one territory, can easily reach a global scale with the advent of the e-book. Large multinational companies like Amazon and Apple have already landed in Europe, and soon they will arrive in the rest of the world. The e-book is not only a change from paper to digital but is also having a substantial impact on reading habits.